2011
DOI: 10.1089/jpm.2010.0235
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine as an Adjuvant Analgesic for Intractable Cancer Pain

Abstract: Dexmedetomidine (Precedex®) is an alpha-2 adrenergic agonist that can produce sedation and analgesia without causing respiratory depression. Its use has been described in patients undergoing mechanical ventilation, sedation for surgical and nonsurgical procedures, and prevention of withdrawal. We describe its use as an adjuvant analgesic in a patient with cancer pain refractory to multiple treatment modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 13 publications
2
21
0
1
Order By: Relevance
“…A retrospective study examining the clinical use of antidepressants and breast cancer development found an association between DMI and increased breast cancer risk (42), consistent with the pro-tumor growth effect shown here. DEX is employed as a sedative to treat cancer pain, adding urgency to delve further into the mechanisms underlying chronic DEX treatment and increased tumor growth and metastasis (43, 44). Finally, our results with DMI and elevated synaptic NE imply a balance between pro-metastatic effects of α 2 -AR and anti-metastatic ß-AR with increased NE release.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study examining the clinical use of antidepressants and breast cancer development found an association between DMI and increased breast cancer risk (42), consistent with the pro-tumor growth effect shown here. DEX is employed as a sedative to treat cancer pain, adding urgency to delve further into the mechanisms underlying chronic DEX treatment and increased tumor growth and metastasis (43, 44). Finally, our results with DMI and elevated synaptic NE imply a balance between pro-metastatic effects of α 2 -AR and anti-metastatic ß-AR with increased NE release.…”
Section: Discussionmentioning
confidence: 99%
“…It is used for procedural sedation, as adjuvant hypnotic during surgery and mechanically ventilated patients in an intensive care setting. There are some preclinical reports 50 to suggest dexmedetomidine has analgesic effects, some clinical evidence on its inhibition of pain conditioning 51 and as adjuvant analgesic for intractable cancer pain 52 but its direct effects on pain remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It is evolving as an adjuvant analgesic, both as intravenous and intrathecal infusion, in cancer pain refractory to multiple treatment modalities. [6162]…”
Section: Perioperative Usementioning
confidence: 99%